Blast resistance of prestressed steel-grouting composite beams under close-in explosions: Experiment and numerical analysis. Issue 7 (May 2022) - Liu, Wenyuan; Fang, Qin; Chen, Li; Li, Zhan; Zhang, Yadong; Xiang, Hengbo
To increase the blast resistance of reinforced concrete or steel–concrete composite structures with long span, an innovative prestressed steel-grouting material composite beam with a hollow web is proposed. In the beam, the flange is filled with grouting material, and an I-type steel web is used to strengthen the shear capacity, and a prestressed tendon is placed in lower flange to improve the flexure resistance. The following three specimens were designed: a double hollow tube, a double tube filled with grouting material, and a prestressed double tube filled with grouting material. The specimens were tested against close-in blast, and overpressure, deformation, and strain were recorded. In order to further understand the blast-resistant performance of the beam, a finite element model was developed by commercial software LS-DYNA. A good agreement between the numerical predictions and test data was observed. It is indicated that the proposed prestressed steel-grouting material composite beam with hollow web exhibits excellent blast-resistant performance.